2020
DOI: 10.1097/inf.0000000000002691
|View full text |Cite
|
Sign up to set email alerts
|

Sacroilitis in Preschool Children: A Case Series and Review of the Literature

Abstract: Pyogenic sacroilitis is an infrequent osteoarticular infection, and its diagnosis is a challenge in young children. A series of 20 cases is described. The median age was 15 months, 75% of them being under 2 years old. Fourteen (70%) reported fever. Refusal to sit was the main reason for consultation. Final diagnosis was confirmed by bone scintigraphy. All patients achieved a complete resolution without sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…22 However, an exclusively oral therapeutic management is yet under evaluation within the pediatric population. 9,[23][24][25] The precedent randomized controlled trials in adults comparing oral to IV therapy for bone infection concluded that oral antibiotic therapy is at least as effective as IV, showing higher adverse event rates and decreased patient satisfaction in the IV groups. 7,8 The Pediatric Rheumatology Unit from the Hospital La Paz, Madrid, started in 2008 a pilot study in which selected children with OAI probably caused by K. kingae who met certain criteria were treated exclusively with oral antibiotic therapy, even if the etiology was not yet determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 However, an exclusively oral therapeutic management is yet under evaluation within the pediatric population. 9,[23][24][25] The precedent randomized controlled trials in adults comparing oral to IV therapy for bone infection concluded that oral antibiotic therapy is at least as effective as IV, showing higher adverse event rates and decreased patient satisfaction in the IV groups. 7,8 The Pediatric Rheumatology Unit from the Hospital La Paz, Madrid, started in 2008 a pilot study in which selected children with OAI probably caused by K. kingae who met certain criteria were treated exclusively with oral antibiotic therapy, even if the etiology was not yet determined.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The Pediatric Rheumatology Unit from the Hospital La Paz, Madrid, started in 2008 a pilot study in which selected children with OAI probably caused by K. kingae who met certain criteria were treated exclusively with oral antibiotic therapy, even if the etiology was not yet determined. 9,[23][24][25] All patients treated entirely orally were managed by scheduled visits to the Pediatric Rheumatology Unit, where the staff provided daily consultation, discussed questions, examined the children and/or performed new arthrocentesis if necessary. After initiation of oral antibiotic therapy, patients are examined within 24-48 hours searching for clinical improvement (decrease in pain, increase in range of motion and disappearance of fever).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study, Peltola et al observed that shorter courses of initial intravenous therapy (2-4 days) followed by oral therapy for 2-3 weeks could be a safe option in children with uncomplicated OAI, especially in children under 3 years in which K.kingae is the main germen identi ed (5,22). However, an exclusively oral therapeutic management is yet under evaluation within the pediatric population (8, [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The Pediatric Rheumatology Unit from the Hospital La Paz, Madrid, started in 2008 a pilot study based on treating selected children with OAI probably caused by K. kingae who meet certain criteria for undergoing an exclusively oral antibiotic therapy, even if the etiology was not yet determined (8, [23][24][25]. All patients treated entirely orally were managed by scheduled visits to the Pediatric Rheumatology Unit, where the staff provided daily consultation, discussed questions, examined the children, and/or performed new arthrocentesis if necessary.…”
Section: Discussionmentioning
confidence: 99%